Kesesuaian dan daya dukung lingkungan untuk pengembangan ekowisata di kawasan hutan Gunung Mareje Utara Kabupaten Lombok Tengah - Nawari, Nawari; Isjoni, Isjoni; Zulkarnaini, Zulkarnaini (Dinamika Lingkungan Indonesia, 2021)
North Mareje Mountain Forest Area (NMMFA) is one of important areas for ecotourism development in Lombok Island. Currently  integrated ecotourism management plan (IEMP) is not available for this area, it has caused land degradation and natural disasters. To support sustainable IEMP establishment, this study was conducted with objectives to analyze land suitability and assessing the environmental carrying capacity of ecotourism development. The study conducted in NMMFA, Serage Village, Central Lombok, NTB during January - March 2020. The data used in this study include attractiveness, landscape naturalness, bio-geophysical limiting factors, accessibility, optimal space requirements and length time of tourist activities. Secondary data compiled from various sources and primary data collected by field observations and interviews. Land suitability analysis used weighted linear combination (WLC), environment carrying capacity analyzed by Douglas Method  (Zacarias et al., 2011) and the evaluation conducted by t-test. Based on the analysis,  explained that land suitable area for ecotourism in  NMMFA is 1.235,2 Ha (75,8% of total area). Effective carrying capacity (ECC) is 32.729 visitors/day. The important indicators contributed to land suitability include soil conservation, tree diversity, visibility and natural attractiveness. T-test analysis shows that the actual landuse for ecotourism smaller than potential area, the average number of tourist visits in the area also smaller than the ECC. It can be concluded if the current land utilization have been meet with land suitability and environmental carrying capacity.